Pemberdayaan Masyarakat Melalui Pemasaran Syari’ah Yang Berkelanjutan Dan Beretika di Pekanbaru - Arfah, Lita; Marro'aini, Marro'aini; Martha Darman, Dian; Sakinah, Nur; Iqbal, Muhammad (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
This community service activity aims to provide information on sharia marketing as a sustainable and ethical community empowerment strategy in Pekanbaru. The sharia approach to marketing emphasizes not only economic profit but also upholds moral values, justice, and social sustainability. Through participatory community service activities, this program involves micro, small, and medium enterprises (MSMEs) in the Air Putih Village of Pekanbaru in developing product marketing strategies that comply with sharia principles. The results of the activity indicate that applying the principles of honesty, transparency, and social responsibility in product promotion and distribution can increase consumer trust, expand market networks, and encourage inclusive economic growth in the community. Furthermore, collaboration between academics, government, and the community plays a crucial role in creating a sustainable sharia marketing ecosystem. The study is expected to reinforce the urgency of integrating Islamic values into daily business practices as a solution for ethical and equitable economic development in urban areas like Pekanbaru